ANALYSIS OF HEAVY EQUIPMENT PRODUCTIVITY IN THE PAVING WORK OF LASTON LAPIS WEAR (AC-WC) ROAD IN THE BANJARMASIN-MARTAPURA ROAD RECONSTRUCTION PROJECT SECTION II - Putri, Ronna Sabilla; Yuliana, Candra; Isramaulana, Aulia (CERUCUK, 2025)
The reconstruction of the Banjarmasin-Martapura Road Section II is carried out to meet the community's needs for better transportation access. In this project, the role of heavy equipment is very important to support the efficiency and effectiveness of the project. This study aims to analyze  the output level of  heavy equipment based on theory and field conditions and identify factors that affect productivity in Laston Lapis Wear (AC-WC) road paving work.The method applied in the analysis of heavy equipment production capacity is  the Time Study Method. This method is used to calculate the standard time of work by collecting data on the amount of time it takes to complete a task.The results of the study show that the production capacity of heavy equipment based on theory reaches 301.06 tons/day and the duration of work is 5 (five) days with the number of heavy equipment Asphalt Sprayer as many as 1 tool, Dump Truck as many as 20 tools, Asphalt Finisher as many as 1 tool, Tandem Roller as many as 1 tool, and Pneumatic Tire Roller a total of 1 tool. Meanwhile, based on the analysis carried out in the field, it was found that the productivity of all heavy equipment was 143 tons/day and the duration of work was 11 (eleven) working days with the number of heavy equipment Asphalt Sprayer as many as 1 tool, Dump Truck as many as 26 tools, Asphalt Finisher as many as 1 tool, Tandem Roller as many as 1 tool, and Pneumatic Tire Roller a total of 1 tool.  The aspects that affect the performance of heavy equipment in this study are material factors, field, heavy equipment conditions, weather and time management.